Treatment of Chronic Hepatitis B - Prasna Pramita; Rino A Gani; Ali Sulaiman (The Indonesian Society for Digestive Endoscopy, 2005)
Chronic hepatitis B is still a major health problem in Indonesia. Unfortunately, to date, treatment of chronic HBV (Hepatitis B virus) infection had not shown satisfactory Result. Monotherapy with alpha interferon or lamivudine have been widely used as treatment of chronic HBV. However, treatment response to Alpha interferon in Asian people was not satisfactory (15% - 20%), while monotherapy with lamivudine was not sufficient to eradicate HBV in chronically infected patients and commonly induce drug resistance. The occurrence of chronic hepatitis B resistant to lamivudine had encouraged development of newer agents such as adefovir, entecavir, emtricitabine and nucleoside analog. New therapeutic strategy using combination therapy should be considered if there is no sufficient response to monotherapy. Keywords: Treatment, chronic hepatitis B, combination therapy